Eco-social contracting for environmental justice: Assessing the effectiveness of community-based natural resource management - Nkosikhona Sibanda (United Nations Research Institute for Social Development (UNRISD), 2024)
This working paper explores the role of community-based natural resource management (CBNRM) in contributing to environmental justice as envisaged by the concept of a new eco-social contract. CBNRM actively involves local communities in sustainable resource management, aligning with the principles of new eco-social contracts. The study analyses key factors influencing CBNRM project outcomes, including influential elites, institutional frameworks, policy dynamics and financing mechanisms. Environmental justice is emphasized as a central concept, highlighting the significance of eco-social contracting in fostering fair and sustainable resource management. Using qualitative and quantitative techniques, case studies from Africa and Asia, and documentary analysis, this paper illustrates how community-based approaches support environmental justice objectives. The paper advocates for inclusive and equitable eco-social contracts to empower local communities in resource management and conservation efforts, addressing challenges related to governance structures, capacity building and financial aspects. The implications of this research are essential for sustainable resource management and inclusive development, aligning with the United Nations 2030 Agenda for Sustainable Development. By examining the transformative potential of CBNRM, this study provides valuable insights for policy makers, practitioners and researchers. Embracing inclusive and equitable approaches, strengthening governance structures and fostering collaborative partnerships is deemed crucial for promoting environmental justice and empowering communities in their journey toward sustainable and just resource management.
Keywords: 330